The role of zinc in the management of covid-19 patients: literature review - Husna, Annisa Khotimatul; Nurhayani, Nurhayani (Universitas 'Aisyiyah Yogyakarta, 2023)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by a new type of coronavirus, SARSCoV-2. Zinc deficiency appears as a potential risk factor in COVID-19 patients. It is known that zinc acts as a facilitator of the body's immune competence. Zinc is also involved in host cell cytokine storms as an immune response to attack pathogens and as a marker of severity in COVID-19. This study aimed to see the effect of giving zinc as antiviral immunity in managing COVID-19 patients. This research method uses a literature review design based on search results for scientific articles in the PubMed, Science Direct, and Proquest databases. Twenty-five articles from Science Direct and 37 from Proquest were analyzed, and eight met the inclusion criteria. It can be concluded that zinc supplementation can be given as adjuvant therapy and works synergistically with the administration of Hydroxychloroquine to reduce disease severity and reduce mortality in COVID-19 patients, especially in hospitalized patients, and is clinically feasible and safe in treatment and prevention. Twenty-five articles from Science Direct, 37 from Proquest, and eight that met the inclusion criteria were analyzed. It can be concluded that zinc supplementation can be given as adjuvant therapy and works synergistically with the administration of Hydroxychloroquine to reduce disease severity and reduce mortality in COVID-19 patients, especially in hospitalized patients, and is clinically feasible and safe in treatment and prevention.